Strengthening emotional ties through parent-child-dyad art therapy : interventions with infants and preschoolers - Proulx, Lucille, 1932- (Jessica Kingsley Publishers, 2003)
Parent-child-dyad art therapy is a new and innovative method of art therapy, in which parent and child share the production of an artwork. Aiming to reinforce or re-establish bonds between children and parents, it provides a space where parents' early unresolved conflicts and children's developmental abilities can be expressed. Lucille Proulx explores many aspects of dyad art therapy including attachment relationship theories, the roles of parents and art therapists in dyad interventions, the importance of the tactile experience and ways in which dyad art therapy could be used to treat other a.